2020
DOI: 10.14218/jcth.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Glecaprevir/Pibrentasvir for Chronic Hepatitis C Patients: A Systematic Review and Meta-analysis

Abstract: Background and Aims: Glecaprevir/pibrentasvir is a pangenotypic regimen recently approved for the treatment of chronic hepatitis C virus (HCV) infection. The objective of the present review was to summarize the findings from clinical trials to understand how patient-related factors influence glecaprevir/pibrentasvir efficacy (sustained virologic response rates at 12 weeks' after treatment [referred to as SVR12]) and safety. Methods: Data from 21 phase III clinical trials were analyzed. Results: The integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…These results were confirmed in another systematic review and meta-analysis of 21 phase 3 clinical trials including 4817 patients with HCV genotype 1-6, which found an SVR12 rate of 97%. 82 Moreover, real-world data from Italy, [83][84][85][86] Germany, 87 Scotland, 88 Austria, 86 Belgium, 86 France, 86 Greece, 86 Poland, 86 Portugal, 86 Switzerland, 86 Israel, 86 Taiwan, 89,90 Japan, [91][92][93][94][95][96][97][98][99][100] and the U.S. 88,101 confirm the efficacy and safety of GLE/PIB in patients with chronic HCV genotype 1-6, including those on hemodialysis 90,92,97,98 and recipients of liver transplantation. 93 Although there have been a few case reports of acute liver injury, including a case of elevated liver enzymes in a non-cirrhotic patient, 102 a case report of severe hyperbilirubinemia and jaundice in a patient with compensated cirrhosis, 103 and a case of jaundice and fatigue, 104 it is difficult to attribute these to GLE/ PIB treatment given the pathology of HCV infection itself.…”
Section: Magellan-3 (mentioning
confidence: 99%
“…These results were confirmed in another systematic review and meta-analysis of 21 phase 3 clinical trials including 4817 patients with HCV genotype 1-6, which found an SVR12 rate of 97%. 82 Moreover, real-world data from Italy, [83][84][85][86] Germany, 87 Scotland, 88 Austria, 86 Belgium, 86 France, 86 Greece, 86 Poland, 86 Portugal, 86 Switzerland, 86 Israel, 86 Taiwan, 89,90 Japan, [91][92][93][94][95][96][97][98][99][100] and the U.S. 88,101 confirm the efficacy and safety of GLE/PIB in patients with chronic HCV genotype 1-6, including those on hemodialysis 90,92,97,98 and recipients of liver transplantation. 93 Although there have been a few case reports of acute liver injury, including a case of elevated liver enzymes in a non-cirrhotic patient, 102 a case report of severe hyperbilirubinemia and jaundice in a patient with compensated cirrhosis, 103 and a case of jaundice and fatigue, 104 it is difficult to attribute these to GLE/ PIB treatment given the pathology of HCV infection itself.…”
Section: Magellan-3 (mentioning
confidence: 99%